If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y = 12 + -3x Solving 4y = 12 + -3x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '4'. y = 3 + -0.75x Simplifying y = 3 + -0.75x
| 2(-9+5x)=52 | | 2(-9+5x)=53 | | 2x-12-2x=4x-12 | | 1/32*12=s | | 3x^4-10x^3-24x^2-6x+5=0 | | 6u^2=-9u | | x-48.12=28.82 | | 6x^2=-9u | | 1.203125=1.375v | | 15g-4=36 | | [x+2]-7=5 | | 1=-3+2x | | -7(4x+7)=-77 | | [x]-10.5=4.3 | | 2(-4h-13)=37*13h | | 3(6z-1)-4(z+5)=7(z+1) | | 4x+12-x-1=1 | | n-31=9 | | t-0.14=28.12 | | -m-3=3m+9 | | 7m+3-4x=-9 | | -4c=9+2c | | 6x+6y=3 | | 6x+3=3x+27 | | 3-w=8w | | -11x=-18-5x | | 3515625*3515625*3515625*3515625*3515625*3515625= | | -1x=165 | | 6+3=x+8 | | 1.83=0.33+p | | j-12.1=7.53 | | 5(3x-2)+12=3(4x+3)+2 |